Noncommunicable Diseases and Global Health Security: Scaling up Action in Humanitarian Crises for Sustainable Recovery - Téa E. Collins; Amanda Karapici; Daria Berlina (Annals of Global Health, 2025)
Emergencies significantly disrupt health systems and hinder regular and timely access to service delivery. Humanitarian assistance during crises tends to prioritize populations’ immediate needs, such as injuries and infectious diseases, rather than noncommunicable diseases (NCDs), which require continuous lifelong care across different specialties and levels of healthcare systems. However, neglecting NCDs in emergency settings can have long-term negative consequences for affected populations, including increased morbidity, unnecessary preventable deaths, and straining already stressed healthcare systems even more. The purpose of this paper is threefold. First, it argues for high-level commitments to integrate NCDs into the Global Health Security Agenda (GHSA) for more effective action toward sustainable recovery. Second, it advocates for a well-coordinated integrated health systems response that holistically tackles NCDs in humanitarian emergencies, focusing on the importance of strengthening pre-crisis infrastructure, quality NCD surveillance data, health workforce, and overall health system readiness. Finally, the paper explores the challenges for effective NCD management, emphasizing the need for multisectoral collaboration, partnerships, and resource mobilization to enhance preparedness, response, and recovery efforts.